Characterization of Harmonic Distortion on the Electric Network Caused by a Battery Charger for Electric Vehicles - CAMACHO , Alejandro Paredes; CORTEZ , Liliana; CORTEZ , Jose Italo; HERNANDEZ , German A Munoz; GONZÁLEZ , Ricardo Alvarez; PEDRO , Garcia Juarez (Asian Journal of Empirical Research, 2013)
The development of new technology on electric vehicles (EV) is intended to counter the damage in the environment, which is a current issue for society. All electric vehicles need a recharging system to store energy whether is from a renewable power source or from an electric power distribution. Most of these systems are connected to the electric network which causes bad quality during the energy supply. In this paper it is shown the effects of a battery charger for EV when connected to the electric network, on the analysis there is an experimental insight and a simulation. In the experimental part, a Schumacher SE-4225 battery charger is presented and its mathematical model evaluated, it takes place the recharging of two types of Lead-acid batteries (a liquid electrolyte/Everstart EXTREME battery and a gel/TROJAN VRLA SG-70 batteries), with a power quality analyzer the harmonic distortion is measured. The simulation part is developed, based on an equivalent circuit’s model of a battery charger, using a MATLAB/Simulink, also presenting the characteristics and electric parameters of each component. They are both processes are analyzed and compared.